Spatiotemporal Hotspots of Juvenile Bigeye and Yellowfin Tuna Catches Under Drifting Fish‐Aggregating Devices in the Eastern Atlantic Ocean to Define Moratorium Strata - Sosthene Alban Valeryn Akia; Loreleï Guéry; Pedro J. Pascual‐Alayón; Daniel Gaertner (Fisheries Management and Ecology, 2025)
To reduce catches of juvenile bigeye and yellowfin tuna, while maintaining skipjack catches under drifting fish aggregating devices (dFAD), we analyzed spatiotemporal distributions of dFAD catches by European purse seiners in the Eastern Atlantic Ocean during 1996–2019. To detect hotspots of juvenile dFAD catches, we: identified periods of maximum abundance using a seasonal sub‐series diagram; normalized monthly FAD catches per unit effort; and used emerging hotspots analysis on spatiotemporal density. Two main spatiotemporal strata were identified in the Guinean Gulf, which could be used to establish moratoria on dFAD fishing. These spatiotemporal strata differed from the existing ICCAT moratorium, which spanned a larger part of the African coast. Our findings also indicated that time‐area closures of dFAD‐fishing lasting 3–4 months in smaller areas could be more effective than the current dFAD moratorium to reduce unwanted bycatch in the Eastern Atlantic region. The two metrics we developed for comparison provided clear and measurable evidence that demonstrated how strategic and data‐informed moratoriums can lead to substantial improvements in conservation.